A Comparative Study Between Palonosetron and Granisetron to Prevent Postoperative Nausea and Vomiting after Laparoscopic Cholecystectomy (TAJ: Journal of Teachers Association, 2018)
Post operative nausea and vomiting is a frequent complication following general anaesthesia and surgery. There is frequently the case of great distress to patient and it is often the worst memory, uncomfortable of their hospital stay. Prolonged post operative nausea and vomiting may cause unexpected physical, metabolic, psychological and economic effects on the patients which slow down their recovery and reduce their confidence in future surgery and anaesthesia. In the present study, we have the incidence of post operative nausea and vomiting in sixty (60) patients undergoing for elective procedure under general anaesthesia. The patients were randomly divided into two groups (group- P, group- G) of thirty (30) patients each.The Patients of group ‘P’ were received intravenous Inj. Palonosetron 75μg and group ‘G’ received intravenous Inj. granisetron 2.5mg (2.5ml) bolus over 30 second just before peritoneal closure. Both group received a standard general anaesthesia. Postoperative analgesia was provided with per rectal diclofenac suppository (50mg) and Inj. Ketorolac Tromethamine 30mg 8 hourly. In the recovery, postoperative room occurrence of nausea and vomiting was assessed for 24 hours. The incidence of post operative nausea and vomiting was reduced in both groups significantly but comparison between these two groups for prevention of PONV(postoperative nausea and vomiting) following elective laparoscopic cholecystectomy surgery is similar. Palonosetron has more prolonged effect than granisetron. There was no evidence of any adverse side effects and whole of the post operative period was smooth.TAJ 2011; 24(2): 118-123